Experimental implementation of algebraic identifier for unbalance parameters in a rotor-bearing system - Quiroz-Bautista, Jesús U.; Arias-Montiel, Manuel; Mendoza-Larios, José G.; Vázquez-Sánchez, Luis (Frontiers in Mechanical Engineering, 2025)
This article presents experimental results on the algebraic identification of the magnitude and phase angle of unbalance in a rotor-bearing system in a Jeffcott configuration. The algebraic identifier is designed based on a simplified mathematical model of the system and it uses only the measurement of the lateral vibration amplitude of the rotor. The proposed algebraic identifier is first validated by numerical simulation. For experimental implementation, a SpectraQuest Machinery Fault and Rotor Dynamics Simulator is used. The designed identifier is evaluated in two scenarios. In the first, the rotor-bearing system is balanced using the traditional coefficients of influence method, after which a known unbalance is induced and compared with the identified magnitude and phase values. In the second case, the unbalance magnitude and phase values obtained by the algebraic identifier from an unknown original unbalanced configuration are used to balance the rotor-bearing system. The vibration amplitude reduction is quantified to evaluate the identified values. The main contribution of this work is the discussion of practical aspects that cannot be appreciated in simulation, but must be considered in the experimental implementation of the algebraic identification method, as they can limit the performance of the designed identifiers.